1979
DOI: 10.1213/00000539-197909000-00007
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics of Intravenous Procaine Infusion in Humans

Abstract: Pharmacokinetic data during and following the continuous intravenous infusion of procaine are lacking. We studied 12 women undergoing hysterectomy during N2O-O2 and narcotic anesthesia. A constant infusion of 2% procaine was administered at a rate of 1 mg/kg/min to six patients (group I) and at a rate of 1.5 mg/kg/min to the other six (group II). Procaine plasma levels were determined by flame ionization gas-liquid chromatography. Using a two-compartment pharmacokinetic model, disposition kinetics were studied… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0

Year Published

1980
1980
2024
2024

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(12 citation statements)
references
References 0 publications
2
10
0
Order By: Relevance
“…In our patients, using a two-cornpartment pharmacokinetic model, procaine had a distribution and an elimination halflife of 2 and 15 minutes, respectively. These values obtained during hypothermia correspond favorably to the 2.5 and 7.7 minutes by Seifen and co-workers (19) at normothermia.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…In our patients, using a two-cornpartment pharmacokinetic model, procaine had a distribution and an elimination halflife of 2 and 15 minutes, respectively. These values obtained during hypothermia correspond favorably to the 2.5 and 7.7 minutes by Seifen and co-workers (19) at normothermia.…”
Section: Discussionsupporting
confidence: 86%
“…No components of Bretschneider's solution other than procaine will cross the blood/brain barrier in the time interval studied. Procaine has abrief half-life and a limited degree of distribution and tissue uptake (19). In our patients, using a two-cornpartment pharmacokinetic model, procaine had a distribution and an elimination halflife of 2 and 15 minutes, respectively.…”
Section: Discussionmentioning
confidence: 76%
“…2b,c). Furthermore, cellular esterase/amidases are unlikely to explain the lack of cellular labeling or weak behavioral activity of A-NK-amide; precedent examples from the literature on local anesthetics show that amidation is correlated with increased in vivo stability (procainamide, lidocaine) over that of procaine444546.…”
Section: Discussionmentioning
confidence: 99%
“…shot of 25 till 50 mg Procaine to reach a systemic action. The pure Procaine infusion was firstly described by SEIFEN et al [37,38] and was mostly used as a continuous treatment in cases of acute pancreatitis [39][40][41] and for epidural anesthesia in infants, children and risk patients, which underlines the low toxicity of the substance [42][43][44][45][46][47][48][49]. O´DONNELL et al reported about the use of procaine infusion to block the cardiac nerves [50].…”
Section: The Procaine-infusion -The Logic Following Of Other Parentermentioning
confidence: 99%